When your problem becomes my problem: The impact of airline IT disruptions on on‐time performance of competing airlines - Tae, C. Jennifer; Pang, Min‐Seok; Greenwood, Brad N. (Strategic Management Journal, 2020)
Abstract Research Summary We study the effect of firm disruptions on competitor performance in the presence of shared resources in the U.S. airline industry. While scholars have investigated both the effects of industry‐wide and firm‐specific disruptions, little work has examined the effect on competitors, who are increasingly reliant on interconnected resources in the digital age. Results from a series of recent information technology (IT) outages indicate that performance is materially affected by a competitor's disruption. While the disruption of a full‐service carrier significantly delays flights of all airlines leveraging its hubs, the exact opposite is observed during the disruption of a low cost carrier. Further, the effect is strongly moderated by the type of airlines reacting to the disruption. Implications for managers and theory are discussed within. Managerial Summary What happens to my operations when a competitor's operations are disrupted? While research has examined how a disrupted firm can recover, little attention has been paid to competitors, except their ability to exploit the disruption for economic gain. This is problematic, as firms increasingly leverage interconnected resources and infrastructure. We show that an airline's IT outages affect on‐time performance of competitors' flights to and from its hub airports. However, the effects depend on both who is disrupted, and who is reacting to that disruption. The disruptions of full‐service carriers (FSCs) delay competitors' flights, but that of a low‐cost carrier (LCC) leads to early arrivals and departures. Further, LCCs are significantly more nimble reacting to disruptions compared to FSCs.